2020
DOI: 10.3390/app10228187
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitivity Analysis of the Damage Behavior of a Leading-Edge Subject to Bird Strike

Abstract: This paper aims to investigate the crashworthiness capability of a commercial aircraft metallic sandwich leading edge, subjected to bird strike events. A sensitivity analysis is presented, aimed to assess the influence of the skin parameters (inner and outer faces and core thicknesses) on the leading-edge crashworthiness and to determine, among the configurations able to withstand a bird strike event, the best compromise in terms of weight and structural performances. In order to easily manage the design param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…The code is widely used in engineering applications and is demonstrated to be suitable for several technical problems [17][18][19][20]. The applied loading conditions are different between unfolded and folded configuration.…”
Section: Optimization Analysismentioning
confidence: 99%
“…The code is widely used in engineering applications and is demonstrated to be suitable for several technical problems [17][18][19][20]. The applied loading conditions are different between unfolded and folded configuration.…”
Section: Optimization Analysismentioning
confidence: 99%
“…Aluminium and its alloys are very interesting in this regard because of their low density, high specific strength to weight ratio and better mechanical properties. 1014 , 1621 The AA7075 grades, in particular, are widely preferred among all grades.AA7075 grades are majorly alloyed with Al-Zn-Mg-Cu elements which possess higher tensile properties, better specific strength, good corrosion resistance, good thermal conductivity, higher fracture toughness and superior energy absorbing capability. 1016 The main problems arising in AA7075 grades during fusion welding processes are (i) solidification hot cracking and (ii) micro segregation of alloying elements in the heat affected zone (HAZ).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have conducted experimental, theoretical, and numerical studies on the ballistic response of aluminium 7xxx grades to high impact velocity projectiles. 714 , 18–23 Mishra et al. 7 studied the ballistic performance of various heat treated AA7055 plates against high velocity projectile impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…V acanfora et al investigated the feasibility and effectiveness of novel thin additive manufactured hybrid metal/ composite lattice structures by the new thin additive are studied, and the results showed that the structure maximizes the energy absorbed through plastic deformation and coating [30]. Francesco Di Caprio et al reported the impact aircraft metallic sandwich leading-edge subjected to a bird strike, and use the model to analyze its energy consumption characteristics [31]. D H Laananen et al established a performance analysis of the energy-absorbing seat configurations for aircraft [32].…”
Section: Introductionmentioning
confidence: 99%